2015
DOI: 10.1515/ersc-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress response in the roadway for the effects of non-steroidal anti-inflammatory drugs

Abstract: Over the past decade, a handful of evidence has been provided that nonsteroidal anti-inflammatory drugs (NSAIDs) display effects on the homeostasis of the endoplasmic reticulum (ER). Their uptake into cells will eventually lead to activation or inhibition of key molecules that mediate ER stress responses, raising not only a growing interest for a pharmacological target in ER stress responses but also important questions how the ER-stress mediated effects induced by NSAIDs could be therapeutically advantageous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 88 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…[ 1,24,25 ] Activation of ER stress signalling PERK/eIF‐2α/ATF‐4/CHOP and/or IRE‐1α/JNK1/2 pathways by indomethacin and diclofenac results in apoptosis in several culture models including primary pig gastric epithelial cells, Huh‐7, H‐4 and U‐87 cells. [ 4,5 ] In this study, we demonstrated that indomethacin and diclofenac caused ER stress‐mediated apoptosis in Caco‐2 cells by activating different arms of ER sensors. These two NSAIDs and the other two known ER stressors tunicamycin and thapsigargin shared a similar apoptosis‐inducing mechanism by activation of PERK/eIF‐2α/ATF‐4/CHOP pathway.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[ 1,24,25 ] Activation of ER stress signalling PERK/eIF‐2α/ATF‐4/CHOP and/or IRE‐1α/JNK1/2 pathways by indomethacin and diclofenac results in apoptosis in several culture models including primary pig gastric epithelial cells, Huh‐7, H‐4 and U‐87 cells. [ 4,5 ] In this study, we demonstrated that indomethacin and diclofenac caused ER stress‐mediated apoptosis in Caco‐2 cells by activating different arms of ER sensors. These two NSAIDs and the other two known ER stressors tunicamycin and thapsigargin shared a similar apoptosis‐inducing mechanism by activation of PERK/eIF‐2α/ATF‐4/CHOP pathway.…”
Section: Discussionmentioning
confidence: 78%
“…[ 3 ] Indomethacin and diclofenac have been linked to increased phosphorylation of ER sensors, particularly pancreatic‐like ER kinase (PERK) and inositol‐requiring enzymes‐1α (IRE‐1α), in various cell models such as human glioma cells. [ 4,5 ] Activation of PERK upregulates the C/EBP homologous transcription factor expression (CHOP), resulting in alteration of apoptotic proteins, mitochondrial dysfunction and apoptosis. [ 6,7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that endoplasmic reticulum stress responses might be associated with SNX10 expression. The ER stress response is involved in NSAID-induced cell death and toxicity 26 , 27 where Ca 2+ -dependent CHOP induction plays an important role 28 . To assess whether NSAIDs elevate intracellular Ca 2+ level in liver cells, we treated NSAIDs on HepG2 cells loaded with fluo-3 AM, the calcium-binding fluorescent dye.…”
Section: Resultsmentioning
confidence: 99%
“…Diclofenac belongs to the class of most frequently prescribed analgesic and anti-inflammatory drugs (NSAIDs) worldwide. Limited literature data indicate the involvement of NSAIDs in ER stress in different cellular systems [ 15 ], but it remains unknown how NSAIDs may affect ER stress in the endothelial cells. The main questions which we intended to answer in the present work were: (1) whether diclofenac can affect the tunicamycin-induced ER stress in endothelial cells and (2) how the drug can modulate the UPR signaling pathways activated under ER stress.…”
Section: Introductionmentioning
confidence: 99%